KAJIAN SOSIOLOGIS BUDAYA KERJA TENAGA PENDIDIK DISMA MUHAMMADIYAH NANGA PINOH - Hutapiadi, Muhamad; supriyadi, Supriyadi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research entitled "Working Culture of Teachers at SMA Muhammadiyah Nanga Pinoh". A common problem in this research is "how is the Working Culture of Teachers at SMA Muhammadiyah Nanga Pinoh". Sub Problems in this research are: 1) How does the working procedure of teachers in working at SMA Muhammadiyah Nanga Pinoh; 2) how the behavior of teachers in working at SMA Muhammadiyah Nanga Pinoh. The method used is descriptive in the form of survey with qualitative approach. Sources of data in this study are primary data and secondary data. Data collection techniques used are direct observation techniques, indirect observation, direct communication and documentary studies (bibliographic) with data collection tools in the form of observation, interviews and documentation. The data obtained from the observation and interview with the informant analysis using interactive data model analysis technique of Miles and Huberman that done through four stages, namely: Data collection, Data Reduction, Display Data, and conclusion / verification. Â The results of the research shows that: 1) the attitude of teachers in working in SMA Muhammadiyah Nanga Pinoh still not done maximally, for example: in conducting the teaching process not yet maximal, not yet complete the task of reporting information in a timely manner, and in the case of wages system has not done fair; 2) the behavior of teachers in the work of SMA Muhammadiyah Nanga Pinoh in carrying out its work is limited to teaching alone, the effort of innovative creation becomes difficult due to dissatisfied and discriminatory treatment (differentiating of wages) for teachers who have long served with new teachers and the standardization of wages has never been adjusted.Â Keywords: working culture; educators